Penerapan Metode Proyek Dalam Meningkatkan Aspek Psikomotorik Murid Dalam Mata Pelajaran Fikih Di MTS YPM Sarirogo Sidoarjo - Fathul Fauzi (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Maximum efforts are needed, by making the best use of the Teaching Process in shaping human beings and to find three domains of Jurisprudence, namely cognitive, affective, and psychomotor domains. One of them is by applying the project method in improving the psychomotor aspects of the Jurisprudence material at Junior High School on YPM Sarirogo Sidoarjo. From the background above, the problem formulation is as follows, 1) How is the application of the project method in improving the psychomotor aspects of students in the Jurisprudence Subject at Junior High School on YPM Sarirogo Sidoarjo?; 2) What are the constraints in implementing the project method in improving the psychomotor aspects of students in the Jurisprudence Subject at Junior High School on YPM Sarirogo Sidoarjo?; 3) What is the solution to the constraints of implementing the project method in improving the psychomotor aspects of students in the Jurisprudence Subject at Junior High School on YPM Sarirogo Sidoarjo?. The application of the project method at at Junior High School on YPM Sarirogo Sidoarjo consists of a problem project and a special training or learning project. The problem project method is differentiated based on its implementation, namely, the problem project method implemented at school and outside the school. While the project method is a special exercise or study. In its implementation, this method in improving the psychomotor aspects is quite good, this can be proven from the results of the average score and student practice scores carried out in 2020